Novel Routes of Potential Hepatitis C Virus Transmission among People Who Inject Drugs: Secondary Blood Exposures Related to Injection Drug Use. (12th May 2021) - Goldshear, Jesse L.; Simpson, Kelsey A.; Kral, Alex H.; Wenger, Lynn D.; Bluthenthal, Ricky N.
Abstract: Background: The US is in the midst of a national Hepatitis C Virus (HCV) epidemic that appears to be driven by new cases among people who inject drugs (PWID). While HCV transmission among PWID is believed to occur mostly through direct sharing of syringes, some infections may be spread via secondary processes and materials involved in injecting. Objectives: Here, we present the prevalence of secondary blood exposures on clothing and nearby surfaces after injection episodes and examine the correlations of these exposures to lifetime HCV infection among a targeted sample of 553 PWID in Los Angeles and San Francisco, California in 2016-18. Results: In multivariate logistic regression models, higher odds of blood on clothing in the last 30 days was significantly ( p < 0.05) associated with lifetime positive HCV status, opioids as primary drug, injecting with others, sharing cookers, and receptive syringe sharing. Higher adjusted odds of blood on nearby surfaces in the last 30 days was significantly associated with lifetime positive HCV status, sharing cookers, and receptive syringe sharing. Native American race was associated with significantly lower adjusted odds of both outcome variables. Conclusions/Importance: Results indicate the relevance of physical and social micro-environments to the potential for blood exposures secondary to injection episodes. Individuals with chronic HCV seropositivity are potentially more likely to expose others to blood due to decreases in the blood's ability to clot. This highlights the need for increased HCV testing at harm reduction sites and increased supply of first aid and wound-care materials to help stop potential blood exposures after injection episodes.